PERLINDUNGAN HUKUM TERHADAP ISTRI YANG MENJADI KORBAN PERSELINGKUHAN DITINJAU DARI UU NO.23/2004 TENTANG PENGHAPUSAN KDRT - alwi habibi; Syarif Lamanasa; Sitti Alfisyahrin Lasori (Unisan Law Review, 2025)
MOHAMAD ALWI HABIBIE. H1119009. LEGAL PROTECTION FOR WIVES AS VICTIMS OF INFIDELITY: A REVIEW OF LAW NO. 23/2004 ON THE ERADICATION OF DOMESTIC VIOLENCEThis study aims to: (1) identify the legal protections available for wives who are victims of infidelity as outlined in Law No. 23/2004 on the Eradication of Domestic Violence, and (2) examine the factors that hinder legal protection for these wives under the same law. The research employs an empirical methodology employing direct involvement in the field. Legal protection encompasses all efforts made to fulfill the rights and aid witnesses and victims, thereby ensuring a sense of security within the legal system. This protection can be categorized into two main forms: preventive and repressive legal protection. Preventive protection seeks to avert legal violations through clear regulations, legal counseling, and oversight by authorities. In contrast, repressive protection involves actions taken after a violation has occurred, such as law enforcement, imposing sanctions on perpetrators, and providing support and rehabilitation for victims. The study identifies two significant factors that hinder legal protection for wives who are victims of infidelity, as reviewed by Law No. 23/2004: the challenges associated with proving psychological violence and economic constraints. Keywords: legal protection, victims of infidelity, domestic violence